A Preliminary Study of Training and Employment of Agricultural Graduates in India - Planning Commission (Planning Commission, 1957)
Increase in agricultural production holds the key to the stability of the Indian economy and the success of it plans for economic development. Agriculture has to provide adequate food for the increasing needs of a growing population, supply the raw materials needed for an expanding industrial economy and make available larger exportable surpluses of agricultural commodities. The first five year plan gave pride of place to agricultural programmes. The increase in production which took place during the First Plan played an important part in ending inflation and preparing the way for a higher rate of development during the Second Five Year Plan.
Planning Commission Scientific and Technical Manpower Division
Planning Commission Scientific and Technical Manpower Division